Penicindopene A, a new indole diterpene from the deep-sea fungus Penicillium sp. YPCMAC1. Issue 20 (18th October 2019) - Liu, Lijun; Xu, Wei; Li, Shumin; Chen, Mengying; Cheng, Yongjun; Yuan, Wangjun; Cheng, Zhongbin; Li, Qin
Abstract: A new indole diterpene, named penicindopene A (1 ), together with seven known compounds (2 – 8 ), was isolated from the deep-sea fungus Penicillium sp. YPCMAC1. The structure of penicindopene A was elucidated by extensive spectroscopic analyses (1 D and 2 D NMR, and HRESIMS data), in addition to the ECD calculations for the assignments of its absolute configuration. Penicindopene A represented the first example of indole diterpenes possessing a 3-hydroxyl-2-indolone moiety, and it exhibited moderate cytotoxicities against A549 and HeLa cell lines with IC50 values of 15.2 and 20.5 µ M, respectively. Graphical Abstract: